Dielectric elastomer actuators based on stretchable and self-healable hydrogel electrodes. Issue 8 (7th August 2019) - Gao, Yang; Fang, Xiaoliang; Tran, Danhquang; Ju, Kuan; Qian, Bo; Li, Jin
Abstract : Dielectric elastomer actuator (DEA) based on dielectric elastomer holds promising applications in soft robotics. Compliant electrodes with large stretchability and high electrical conductivity are the vital components for the DEAs. In this study, a type of DEA was developed using carbon nanotube/polyvinyl alcohol (CNT/PVA) hydrogel electrodes. The CNT/PVA hydrogel electrodes demonstrate a stretchability up to 200% with a small relative resistance change of approximately 1.2, and a self-healing capability. The areal strain of the DEA based on the CNT/PVA hydrogel electrodes is more than 40%, much higher than the ones based on pure PVA electrodes.